STUDI IDENTIFIKASI PENGELOLAAN AIR LIMBAH DOMESTIK KECAMATAN SEMARANG TENGAH, SEMARANG TIMUR, GAYAMSARI, DAN GENUK KOTA SEMARANG - Nureka Yuliani; Wiharyanto Oktiawan; Mochtar Hadiwidodo (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTNowadays the society of Middle Semarang, East Semarang, Gayamsari, and Genuk subdistrict are using on site system with water closet for sanitation infrastructure and throw away the grey water to drainage. Domestic waste water management isn’t in line with growth population and city function development, and as the concequence is environment quality degradation. This research is for knowing domestic waste water management condition from four subdistricts with investigate five aspects (organization, operational, funding, legal, and society participation). The result of operational aspect analysis is off site system for Middle Semarang, East Semarang, Gayamsari, and partly of Genuk. Whereas on site system with septic tank can be applied at Trimulyo, Terboyo Wetan, and Terboyo Kulon (Genuk subdistrict). Funding aspect alternative is partly of APBD and partly of society toll and organize local independent group which controlling finance management. The result of organization aspect analysis alternative is a organization concept from city level till RW. Based on SWOT analysis for legal and society participation is produce an legal concept, increase socialiszation to society and involve private participation.